PENDAPATAN PETANI KELAPA SAWIT KECAMATAN TRIPA MAKMUR KABUPATEN NAGAN RAYA - Aswin Nasution; Sri Handayani; Liston Siringo Ringo; Sufriadi Sufriadi (JURNAL EKOMBIS, 2018)
Oil palm is a plantation crop that can improve the farmer’s economy,reducing poverty and encouraging rural development through farmer incomes. Research conducted in Tripa Makmur Sub District and Nagan Raya District shows thatoil palm plantation business is feasible, because it provides operating income of Rp. 26.931.466, - / Hectare /year with R/Cratio 2.88, but farmers have not done a good efficiencywhen compared with other regions such as in South Sumatra that have R/C ratio 3.18-3.25.Variable of plantation area, plant age, fertilization cost, plant maintenance cost, harvest cost, production and price of FFB strongly influence farmer's income;and simultaneously significantly affect farmers' incomes;partially plantation area,harvest cost, FFB productionhave a positive and significant effectto farmer's income;variable of fertilizer costand maintenance have a significant and negative impact to farmers' income. The plant age variable and price of FFB did not impact to the farmer's income. Keywords: Farmers' income,  small holder, palm oil,  production factors